Epidemiological Investigation of Porcine Pseudorabies Virus in Hebei Province, China, 2017–2018 - Zhang, Cheng; Cui, Huan; Zhang, Wuchao; Meng, Lijia; Chen, Ligong; Wang, Zhongyi; Zhao, Kui; Chen, Zhaoliang; Qiao, Sina; Liu, Juxiang; Guo, Zhendong; Dong, Shishan (Frontiers in Veterinary Science, 2022)
Pseudorabies (PR) is a serious disease affecting the pig industry in China, and it is very important to understand the epidemiology of pseudorabies virus (PRV). In the present study, 693 clinical samples were collected from Bartha-K61 vaccinated pigs with symptoms of suspected PRV infection between January 2017 and December 2018. All cases were referred for full clinical autopsy with detailed examination of histopathological examination, virus isolation and genetic evolution analysis of the PRV glycoprotein E (gE) gene. In addition, PRV gE antibodies in 3,449 serum samples were detected by the enzyme-linked immunosorbent assay (ELISA). The clinical data revealed that abortion and stillbirth are the most frequent appearances in pregnant sows of those cases. Histopathological examination exhibited a variety of pathological lesions, such as lobar pneumonia, hepatitis, lymphadenitis, nephritis, and typical nonsuppurative encephalitis. A total of 248 cases tested positive for the PRV gE gene. 11 PRV variants were isolated and confirmed by gE gene sequencing and phylogenetic analysis. These strains had 97.1%-100.0% nucleotide homology with the PRV reference strains. Notably, the isolated strains were highly homologous and clustered in the same branch as HSD-1/2019, which caused human acute encephalitis. Serological tests showed that the positive rate of PRV gE antibody in the 3449 serum samples collected from the Hebei Province was 46.27%. In conclusion, PRV variant strains Are high prevalence in the Hebei Province, which not only causes huge economic losses to the breeding industry but also potentially poses a threat to public health.